Pilot study Al-Maahirah app in enhancing Arabic learning: A case study at Al-Khairiyah High School, Indonesia - Naqiyah, Neni; Muassomah, Muassomah; Mufidah, Nuril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Arabic language proficiency of students at Al-Khairiyah Senior High School Kelapian Banten appears to be hindered by several factors, including a lack of interactive learning tools such as Android-based applications, gaps in instructional content, low student engagement, limited teacher training, and the absence of supplementary educational resources like LKPD. Even though Azzahra stated, that Android-based Arabic language worksheets are quite effective in improving students' Arabic learning outcomes. A study was conducted to evaluate the impact of the